Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

A content analysis of parents’ reflections on pathogenic and uncertain pediatric oncology germline sequencing results - Katianne M. Howard Sharp; Mary Egan Clark; Niki Jurbergs; Annastasia Ouma; Lynn Harrison; Leslie Taylor; Kayla Hamilton; Rose B. McGee; Regina Nuccio; Stacy Hines-Dowell; Jami S. Gattuso; Michelle Pritchard; et al. (Familial Cancer, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Investigating Fire–Atmosphere Interaction in a Forest Canopy Using Wavelets - Ajinkya Desai; Clément Guilloteau; Warren E. Heilman; Joseph J. Charney; Nicholas S. Skowronski; Kenneth L. Clark; Michael R. Gallagher; Efi Foufoula-Georgiou; Tirtha Banerjee (Boundary-Layer Meteorology, 2024)
Wildland fire–atmosphere interaction generates complex turbulence patterns, organized across multiple scales, which inform fire-spread behaviour, firebrand transport, and smoke dispersion. Here, we utilize wavelet-based techniques to explore the characteristic temporal scales associated with coherent patterns in the measured temperature and the turbulent fluxes during a prescribed wind-driven (heading) surface fire beneath a forest canopy. We use temperature and velocity measurements from tower-mounted sonic anemometers at multiple heights. Patterns in the wavelet-based energy density of the measured temperature plotted on a time–frequency plane indicate the presence of fire-modulated ramp–cliff structures in the low-to-mid-frequency band (0.01–0.33 Hz), with mean ramp durations approximately 20% shorter and ramp slopes that are an order of magnitude higher compared to no-fire conditions. We then investigate heat- and momentum-flux events near the canopy top through a cross-wavelet coherence analysis. Briefly before the fire-front arrives at the tower base, momentum-flux events are relatively suppressed and turbulent fluxes are chiefly thermally-driven near the canopy top, owing to the tilting of the flame in the direction of the wind. Fire-induced heat-flux events comprising warm updrafts and cool downdrafts are coherent down to periods of a second, whereas ambient heat-flux events operate mainly at higher periods (above 17 s). Later, when the strongest temperature fluctuations are recorded near the surface, fire-induced heat-flux events occur intermittently at shorter scales and cool sweeps start being seen for periods ranging from 8 to 35 s near the canopy top, suggesting a diminishing influence of the flame and increasing background atmospheric variability thereat. The improved understanding of the characteristic time scales associated with fire-induced turbulence features, as the fire-front evolves, will help develop more reliable fire behaviour and scalar transport models.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Carbon dynamics of prescribed fire in pine- and oak-dominated forests on the mid-Atlantic coastal plain, USA - Kenneth L. Clark; Nicholas S. Skowronski; Michael R. Gallagher (Forest Ecology and Management, 2024)

Two decades of carbon dynamics in an actively-managed, naturally-regenerated longleaf/slash pine forest - Rosvel Bracho; Timothy A. Martin; Jason G. Vogel; Wendell P. Cropper Jr; Gerardo Celis; Kenneth Clark; Henry L. Gholz; Gregory Gorman; Henry W. Loescher; Thomas L. Powell; Scott Sager; Maryada Shrestha; et al. (Forest Ecology and Management, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

The effects of forest composition and management on evapotranspiration in the New Jersey Pinelands - Bernard N. Isaacson; Yun Yang; Martha C. Anderson; Kenneth L. Clark; Jason C. Grabosky (Agricultural and Forest Meteorology, 2023)

Helium isotope evidence for mixing of mantle-derived fluids and deeply penetrating surface waters in an obducted peridotite massif - Carl Swindle; Doug Clark; Kenneth A. Farley (Geochimica et Cosmochimica Acta, 2023)

Features of turbulence during wildland fires in forested and grassland environments - Ajinkya Desai; Warren E. Heilman; Nicholas S. Skowronski; Kenneth L. Clark; Michael R. Gallagher; Craig B. Clements; Tirtha Banerjee (Agricultural and Forest Meteorology, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Empirical nitrogen and sulfur critical loads of U.S. tree species and their uncertainties with machine learning - Nathan R. Pavlovic; Shih Ying Chang; Jiaoyan Huang; Kenneth Craig; Christopher Clark; Kevin Horn; Charles T. Driscoll (Science of The Total Environment, 2023)

Correction: Evaluating ecosystem services for agricultural wetlands: a systematic review and meta-analysis - Eric Asare; Chrystal Mantyka-Pringle; Erik Anderson; Kenneth Belcher; Robert Clark (Wetlands Ecology and Management, 2022)

Evaluating ecosystem services for agricultural wetlands: a systematic review and meta-analysis - Asare Eric; Mantyka-Pringle Chrystal; Anderson Erik; Belcher Kenneth; Clark Robert (Wetlands Ecology and Management, 2022)
Globally, the extent of inland wetlands has declined by approximately 70% since the start of the twentieth century, resulting in the loss of important wetland-associated ecosystem services. We evaluate the drivers of wetland values in agricultural landscapes to increase the effectiveness and reliability of benefit transfer tools to assign values to local wetland services. We reviewed 668 studies that analyzed wetland ecosystem services within agricultural environments and identified 45 studies across 22 countries that provided sufficient economic information to be included in a quantitative meta-analysis. We developed meta-regression models to represent provisioning and regulating wetland ecosystem services and identify the main drivers of these ecosystem service categories. Provisioning wetland ecosystem service values were best explained (direction of effects in parenthesis) by high-income variable (+), peer-reviewed journal publications (+), agricultural total factor productivity index (−) and population density (+), while agricultural total factor productivity index (−), income level ( +) and wetland area (−) had significant effects on regulating wetland ecosystem service values. Our models can help estimate wetland values more reliably across similar regions because they have significantly lower transfer errors (66 and 185% absolute percentage error for the provisioning and regulating models, respectively) than the errors from unit value transfers. Model predicted wetland values ($/Ha/Year) range from $0.62 to $11,216 for regulating services and $0.95 to $2,122 for provisioning services and vary based on the differences in the levels of the variables (in the wetland locations) that best explained the estimated models.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Extinction risk of the endemic vascular flora of Kauai, Hawaii, based on IUCN assessments - Nina Rønsted; Seana K. Walsh; Margaret Clark; Merlin Edmonds; Tim Flynn; Scott Heintzman; Alexander Loomis; David Lorence; Uma Nagendra; Ben Nyberg; Michael Opgenorth; Lauren Weisenberger; et al. (Conservation Biology, 2022)
The International Union for Conservation of Nature's Red List of Threatened Species (IUCN Red List) is the world's most comprehensive information source on the global conservation status of species. Governmental agencies and conservation organizations increasingly rely on IUCN Red List assessments to develop conservation policies and priorities. Funding agencies use the assessments as evaluation criteria, and researchers use meta‐analysis of red‐list data to address fundamental and applied conservation science questions. However, the circa 143,000 IUCN assessments represent a fraction of the world's biodiversity and are biased in regional and organismal coverage. These biases may affect conservation priorities, funding, and uses of these data to understand global patterns. Isolated oceanic islands are characterized by high endemicity, but the unique biodiversity of many islands is experiencing high extinction rates. The archipelago of Hawaii has one of the highest levels of endemism of any floristic region; 90% of its 1367 native vascular plant taxa are classified as endemic. We used the IUCN's assessment of the complete single‐island endemic (SIE) vascular plant flora of Kauai, Hawaii, to assess the proportion and drivers of decline of threatened plants in an oceanic island setting. We compared the IUCN assessments with federal, state, and other local assessments of Kauai species or taxa of conservation concern. Finally, we conducted a preliminary assessment for all 1044 native vascular plants of Hawaii based on IUCN criterion B by estimating area of occupancy, extent of occurrence, and number of locations to determine whether the pattern found for the SIE vascular flora of Kauai is comparable to the native vascular flora of the Hawaiian Islands. We compared our results with patterns observed for assessments of other floras. According to IUCN, 256 SIE vascular plant taxa are threatened with extinction and 5% are already extinct. This is the highest extinction risk reported for any flora to date. The preliminary assessment of the native vascular flora of Hawaii showed that 72% (753 taxa) is threatened. The flora of Hawaii may be one of the world's most threatened; thus, increased and novel conservation measures in the state and on other remote oceanic islands are urgently needed.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Integrating team science into interdisciplinary graduate education: an exploration of the SESYNC Graduate Pursuit - Kenneth E. Wallen; Karen Filbee-Dexter; Jeremy B. Pittman; Stephen M. Posner; Steven M. Alexander; Chelsie L. Romulo; Drew E. Bennett; Elizabeth C. Clark; Stella J.M. Cousins; Bradford A. Dubik; Margaret Garcia; Heather A. Haig; et al. (Journal of Environmental Studies and Sciences, 2019)

Assessing the interplay between canopy energy balance and photosynthesis with cellulose δ18O: large-scale patterns and independent ground-truthing - Brent R. Helliker; Xin Song; Michael L. Goulden; Kenneth Clark; Paul Bolstad; J. William Munger; Jiquan Chen; Asko Noormets; David Hollinger; Steve Wofsy; Timothy Martin; Dennis Baldocchi; et al. (Oecologia, 2018)

High-depth whole genome sequencing of an Ashkenazi Jewish reference panel: enhancing sensitivity, accuracy, and imputation - Todd Lencz; Jin Yu; Cameron Palmer; Shai Carmi; Danny Ben-Avraham; Nir Barzilai; Susan Bressman; Ariel Darvasi; Judy H. Cho; Lorraine N. Clark; Zeynep H. Gümüş; Vijai Joseph; et al. (Human Genetics, 2018)

A philosophical basis for hydrological uncertainty - Grey S. Nearing; Yudong Tian; Hoshin V. Gupta; Martyn P. Clark; Kenneth W. Harrison; Steven V. Weijs (Hydrological Sciences Journal, 2016)

Microsatellite records for volume 8, issue 2 - Dareen Almojil; Maria Cristina Arias; Rochelle R. Beasley; Yiyong Chen; Rulon W. Clark; Yinghui Dong; Zhiguo Dong; Natalie Forsdick; Elaine Françoso; E. González-Ortegón; A. M. González-Tizón; Linsheng Gui; et al. (Conservation Genetics Resources, 2016)

Compositional shifts in C osta R ican forests due to climate‐driven species migrations - Kenneth J. Feeley; Johanna Hurtado; Sassan Saatchi; Miles R. Silman; David B. Clark (Global Change Biology, 2013)
Species are predicted to shift their distributions upslope or poleward in response to global warming. This prediction is supported by a growing number of studies documenting species migrations in temperate systems but remains poorly tested for tropical species, and especially for tropical plant species. We analyzed changes in tree species composition in a network of 10 annually censused 1‐ha plots spanning an altitudinal gradient of 70–2800 m elevation in Costa Rica. Specifically, we combined plot data with herbarium records (accessed through GBIF ) to test if the plots' community temperature scores ( CTS , average thermal mean of constituent species weighted by basal area) have increased over the past decade as is predicted by climate‐driven species migrations. In addition, we quantified the contributions of stem growth, recruitment, and mortality to the observed patterns. Supporting our a priori hypothesis of upward species migrations, we found that there have been consistent directional shifts in the composition of the plots, such that the relative abundance of lowland species, and hence CTS , increased in 90% of plots. The rate of the observed compositional shifts corresponds to a mean thermal migration rate ( TMR ) of 0.0065 °C yr −1 (95% CI = 0.0005–0.0132 °C yr −1 ). While the overall TMR is slower than predicted based on concurrent regional warming of 0.0167 °C yr −1 , migrations were on pace with warming in 4 of the 10 plots. The observed shifts in composition were driven primarily by mortality events (i.e., the disproportionate death of highland vs. lowland species), suggesting that individuals of many tropical tree species will not be able to tolerate future warming and thus their persistence in the face of climate change will depend on successful migrations. Unfortunately, in Costa Rica and elsewhere, land area inevitably decreases at higher elevations; hence, even species that are able to migrate successfully will face heightened risks of extinction.

Effects of a prescribed fire on water use and photosynthetic capacity of pitch pines - Heidi J. Renninger; Kenneth L. Clark; Nicholas Skowronski; Karina V. R. Schäfer (Trees, 2013)

Psychostimulant Abuse and Neuroinflammation: Emerging Evidence of Their Interconnection - Kenneth H. Clark; Clayton A. Wiley; Charles W. Bradberry (Neurotoxicity Research, 2013)

(2-Methoxyethoxy)acetic acid: a urinary biomarker of exposure for jet fuel JP-8 - Clayton B’Hymer; Patricia Mathias; Edward Krieg; Kenneth L. Cheever; Christine A. Toennis; John C. Clark; James S. Kesner; Roger L. Gibson; Mary Ann Butler (International Archives of Occupational and Environmental Health, 2012)

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Transient Supplementation of Anabolic Growth Factors Rapidly Stimulates Matrix Synthesis in Engineered Cartilage - Kenneth W. Ng; Christopher J. O’Conor; Lindsay E. Kugler; James L. Cook; Gerard A. Ateshian; Clark T. Hung (Annals of Biomedical Engineering, 2011)

Carbon Sequestration in the New Jersey Pine Barrens Under Different Scenarios of Fire Management - Robert M. Scheller; Steve Van Tuyl; Kenneth L. Clark; John Hom; Inga La Puma (Ecosystems, 2011)

Native herbivore exerts contrasting effects on fire regime and vegetation structure - José L. Hierro; Kenneth L. Clark; Lyn C. Branch; Diego Villarreal (Oecologia, 2011)

Do Current Animal Models of Intracerebral Hemorrhage Mirror the Human Pathology? - Opeolu Adeoye; Joseph F. Clark; Pooja Khatri; Kenneth R. Wagner; Mario Zuccarello; Gail J. Pyne-Geithman (Translational Stroke Research, 2011)

Impact of insect defoliation on forest carbon balance as assessed with a canopy assimilation model - KARINA V. R. SCHÄFER; KENNETH L. CLARK; NICHOLAS SKOWRONSKI; ERIK P. HAMERLYNCK (Global Change Biology, 2010)
Disturbances such as fire, hurricanes, and herbivory often result in the net release of CO 2 from forests to the atmosphere, but the magnitude of carbon (C) loss is poorly quantified and difficult to predict. Here, we investigate the carbon balance of an oak/pine forest in the New Jersey Pine Barrens using the Canopy Conductance Constrained Carbon Assimilation (4C‐A) model. The 4C‐A model utilizes whole‐tree sap‐flux and leaf‐level photosynthetic gas exchange measurements at distinct canopy levels to estimate canopy assimilation. After model parameterization, sensitivity analyses, and evaluation against eddy flux measurements made in 2006, the model was used to predict C assimilation for an undisturbed year in 2005, and in 2007 when the stand was completely defoliated for 2–3 weeks during an infestation of gypsy moths ( Lymantria dispar L.). Following defoliation, only 50% of the foliage reemerged in a second flush. In 2007, canopy net assimilation ( A nC ), as modeled with the 4C‐A, was reduced to approximately 75% of A nC in 2006 (940 vs. 1240 g C m −2 a −1 ). Overall, net primary production (NPP) in 2007 was approximately 240 g C m −2 a −1 (vs. 250 g C m −2 a −1 in 2006), with 60% of NPP allocated to foliage production, a short‐term carbon pool. Woody biomass accumulation, a long‐term carbon pool, was reduced by 20% compared with the previous year (72 vs. 57 g C m −2 a −1 in 2006 and 2007, respectively). The overall impact of the defoliation spanned 21% of upland forests (320 km 2 ) in the New Jersey Pine Barrens, representing a significant amount of overall C not being taken up from the atmosphere by the forest, thus not accumulated in the biosphere.

Invasive insects impact forest carbon dynamics - KENNETH L. CLARK; NICHOLAS SKOWRONSKI; JOHN HOM (Global Change Biology, 2010)
Invasive insects can impact ecosystem functioning by altering carbon, nutrient, and hydrologic cycles. In this study, we used eddy covariance to measure net CO 2 exchange with the atmosphere (NEE), and biometric measurements to characterize net ecosystem productivity (NEP) in oak‐ and pine‐dominated forests that were defoliated by Gypsy moth ( Lymantria dispar L.) in the New Jersey Pine Barrens. Three years of data were used to compare C dynamics; 2005 with minimal defoliation, 2006 with partial defoliation of the canopy and understory in a mixed stand, and 2007 with complete defoliation of an oak‐dominated stand, and partial defoliation of the mixed and pine‐dominated stands. Previous to defoliation in 2005, annual net CO 2 exchange (NEE yr ) was estimated at −187, −137 and −204 g C m −2 yr −1 at the oak‐, mixed‐, and pine‐dominated stands, respectively. Annual NEP estimated from biometric measurements was 108%, 100%, and 98% of NEE yr in 2005 for the oak‐, mixed‐, and pine‐dominated stands, respectively. Gypsy moth defoliation strongly reduced fluxes in 2006 and 2007 compared with 2005; NEE yr was −122, +103, and −161 g C m −2 yr −1 in 2006, and +293, +129, and −17 g C m −2 yr −1 in 2007 at the oak‐, mixed‐, and pine‐dominated stands, respectively. At the landscape scale, Gypsy moths defoliated 20.2% of upland forests in 2007. We calculated that defoliation in these upland forests reduced NEE yr by 41%, with a 55% reduction in the heavily impacted oak‐dominated stands. ‘Transient’ disturbances such as insect defoliation, nonstand replacing wildfires, and prescribed burns are major factors controlling NEE across this landscape, and when integrated over time, may explain much of the patterning of aboveground biomass and forest floor mass in these upland forests.

Carbon exchange of a mature, naturally regenerated pine forest in north Florida - THOMAS L. POWELL; HENRY L. GHOLZ; KENNETH L. CLARK; GREGORY STARR; WENDELL P. CROPPER; TIMOTHY A. MARTIN (Global Change Biology, 2008)
We used eddy covariance and biomass measurements to quantify the carbon (C) dynamics of a naturally regenerated longleaf pine/slash pine flatwoods ecosystem in north Florida for 4 years, July 2000 to June 2002 and 2004 to 2005, to quantify how forest type, silvicultural intensity and environment influence stand‐level C balance. Precipitation over the study periods ranged from extreme drought (July 2000–June 2002) to above‐average precipitation (2004 and 2005). After photosynthetic photon flux density (PPFD), vapor pressure deficit (VPD) >1.5 kPa and air temperature 2 exchange (NEE day ) and reduced the magnitude of midday CO 2 exchange by >5 μmol CO 2 m −2 s −1 . Analysis of water use efficiency indicated that stomatal closure at VPD>1.5 kPa moderated transpiration similarly in both drought and wet years. Night‐time exchange (NEE night ) was an exponential function of air temperature, with rates further modulated by soil moisture. Estimated annual net ecosystem production (NEP) was remarkably consistent among the four measurement years (range: 158–192 g C m −2 yr −1 ). In comparison, annual ecosystem C assimilation estimates from biomass measurements between 2000 and 2002 ranged from 77 to 136 g C m −2 yr −1 . Understory fluxes accounted for approximately 25–35% of above‐canopy NEE over 24‐h periods, and 85% and 27% of whole‐ecosystem fluxes during night and midday (11:00–15:00 hours) periods, respectively. Concurrent measurements of a nearby intensively managed slash pine plantation showed that annual NEP was three to four times greater than that of the Austin Cary Memorial Forest, highlighting the importance of silviculture and management in regulating stand‐level C budgets.

Culture Duration Modulates Collagen Hydrolysate-Induced Tissue Remodeling in Chondrocyte-Seeded Agarose Hydrogels - Kenneth W. Ng; Justin D. Saliman; Evan Y. Lin; Lauren Y. Statman; Lindsay E. Kugler; Sean B. Lo; Gerard A. Ateshian; Clark T. Hung (Annals of Biomedical Engineering, 2007)

The effects of scale: variation in the APOA1/C3/A4/A5 gene cluster - Andrew G. Clark; Deborah A. Nickerson; Kenneth M. Weiss; Veikko Salomaa; Eric Boerwinkle; Stephanie M. Fullerton; Anne V. Buchanan; Vibhor A. Sonpar; Jari H. Stengrd; Joshua D. Smith; Scott L. Taylor; Christopher S. Carlson (Human Genetics, 2004)

Population structure and secondary productivity of Limnodrilus hoffmeisteri (Claparede) and Branchiura sowerbyi Beddard in the profundal zone of Lake Naivasha, Kenya - Phil Raburu; Kenneth M. Mavuti; David M. Harper; Frank L. Clark (Hydrobiologia, 2002)

Sequence polymorphism at the human apolipoprotein AII gene (APOA2): unexpected deficit of variation in an African-American sample - Stephanie M. Fullerton; Andrew G. Clark; Kenneth M. Weiss; Scott L. Taylor; Jari H. Stengård; Veikko Salomaa; Eric Boerwinkle; Deborah A. Nickerson (Human Genetics, 2002)

Evaluation of Modeled Carbon Fluxes for a Slash Pine Ecosystem: SPM2 Simulations Compared to Eddy Flux Measurements - Kenneth L. Clark; Wendell P. Cropper; Henry L. Gholz (Forest Science, 2001)
A process-based model (SPM2) was developed to simulate net hourly exchanges of carbon for slash pine (Pinus elliottii var. elliottii) ecosystems in north-central Florida, and simulated values were compared to those obtained using eddy covariance measurements above the canopy. The SPM2 simulated relatively low hourly rates of net carbon exchange at high irradiance during the day, especially during the month of May. This discrepancy contributed the most to differences between the two approaches, and suggests that the model underestimates the maximum rate of leaf-level net photosynthesis during the period of rapid growth in the spring. The SPM2 also simulated lower net carbon release during the nighttime across the range of air temperatures, relative to eddy covariance measurements. As a result of these discrepancies, accumulated daytime and nighttime sums were quite different between the two approaches. However, once results were aggregated over 24 hr, differences between simulations and measurements were insignificant at all but the highest and lowest daily net carbon gain values. Annual estimates for 1996 were similar: 693, 719, and 745 g C m-2 yr-1 for the SPM2 model, eddy covariance measurements and mass balance measurements, respectively. This model evaluation has lead to specific research questions for guiding further model development. FOR. Sci. 47(1):52–59.

Spatial Variability of Turbulent Fluxes in the Roughness Sublayer of an Even-Aged Pine Forest - Gabriel Katul; Cheng-I Hsieh; David Bowling; Kenneth Clark; Narasinha Shurpali; Andrew Turnipseed; John Albertson; Kevin Tu; Dave Hollinger; Bob Evans; Brian Offerle; Dean Anderson; et al. (Boundary-Layer Meteorology, 1999)

Soil CO2 efflux and its spatial variation in a Florida slash pine plantation - C. Fang; John B. Moncrieff; Henry L. Gholz; Kenneth L. Clark (Plant and Soil, 1998)

Isolation of Functional RNA from Periderm Tissue of Potato Tubers and Sweet Potato Storage Roots - David L. Scott; Clarence W. Clark; Kenneth L. Deahl; Channapatna S. Prakash (Plant Molecular Biology Reporter, 1998)

Simulating smallmouth bass reproductive success in reservoirs - Mark E. Clark; Kenneth A. Rose; James A. Chandler; Tracy J. Richter; Donald J. Orth; Webster Van Winkle (Environmental Biology of Fishes, 1998)

Second messenger and cAMP-dependent protein kinase responses to dehydration and anoxia stresses in frogs - Clark P. Holden; Kenneth B. Storey (Journal of Comparative Physiology B, 1997)